Geomorphological evolution of the Petrovaradin Fortress Palaeolithic site (Novi Sad, Serbia). (September 2021) - Marković, Slobodan B.; Vandenberghe, Jef; Stevens, Thomas; Mihailović, Dušan; Gavrilov, Milivoj B.; Radaković, Milica G.; Zeeden, Christian; Obreht, Igor; Perić, Zoran M.; Nett, Janina J.; Lehmkuhl, Frank
Abstract: Two phases of archaeological investigation were performed in the Novi Sad City Museum at Petrovaradin Fortress. In this study, we summarize the results of geo-archaeological investigations of the second period of excavation inside the Novi Sad City Museum building. The fortress is situated on a Danube terrace with the top of the bedrock at ca.123 m asl. The investigated section consists of undisturbed fine-sandy silt. The grain-size distribution of the sediments indicates clearly its alluvial reworking but shows also a general similarity with typical primary loess in the region. All analyzed proxies indicate slightly stronger weathering in the upper part of the profile. Luminescence ages suggest that the investigated sequence covers the last glacial period and the terrace presumably formed during MIS 4. Subsequently, the Danube started its incision at the start of the next warmer period (MIS 3) onward. This terrace age and elevation enable us to derive an uplift rate of the terrace of ca. 0.73 mm/a for the last 60 ka, which seems to increase towards the present. Basal loessic material, in which artifacts occur, likely in the reworked position, indicate that the area close to today's Petrovaradin Fortress was already inhabited in MIS 5.